Limites da intervenção jurisdicional nas políticas públicas ambientais - Gomes, Artur Amaral (2017)
The environmental crisis has been and continues to be the starting point of a series of changes which main purpose is to change the way man relates to the environment, transforming him into a true ecological subject and overcoming the idea that man is, above all, the owner of nature. To help in this phase of overcoming, the environmental issue has invaded the legal sector, forcing many legal systems to embrace it. In Brazil, the fundamental right to ecologically balanced environment present in the Federal Constitution of 1988 represents an important advance that still requires greater efforts to achieve an adequate and sufficient level of social efficiency. The formulation and implementation of environmental public policies is a field where the Brazilian Public Administration is still crawling and making mistakes, especially the incorrect balance between economic and environmental interests. Such “mistakes” amount to unconstitutionalities and illegalities that cannot last in a country that still has so much natural environment as Brazil. In order to repeal and correct such misconceptions, it is the responsibility of the Judiciary to carry out the control of environmental public policies, which implies a real judicial intervention in the political process, an activity that has become the target of innumerable criticisms and opposing arguments that try to reap the legitimacy of the jurisdictional action. However, although is possible to dismiss such allegations of violations, from them it is also possible to identify necessary limits to the Judiciary’s action in order to preserve the legitimacy of judicial control, which raises a discussion about the controversial judicial activism. The present work used the bibliographic research method to effectively evaluate the arguments against judicial intervention in the political process, as well as what limits can be drawn from such claims, initially addressing the environmental crisis, the role of man in it, the status of environmental law in Brazil and the clash between development and sustainability. Afterwards, an examination of what are environmental public policies and on what their effectiveness depends, as well as a brief exposition of the main Brazilian laws that provide guides for the State’s action. Next, an evaluation of the phenomenon of the judicialization of politics, duly accompanied by the main alleged violations that its fortification causes. Finally, an approach on the limits necessary for judicial intervention in the political process, highlighting the figure of judicial activism and the possibility of seeing it as something positive or negative, which depends on the State’s action to implement the social and environmental project that the Constitution presents. Keywords: Environment. Public policies. Judicial intervention.Judicial activism. Environmental law. PPGDA/UEA.